FREQUENCY AND FACT: LEARNING ABOUT THE WORLD THROUGH A CORPUS OF WORLD-ENGLISHES - Snefjella, Bryor (My University, 2014)
Two studies are presented, linking word-frequency information within the Global Corpus of Web-based English to real world facts. The first study concerns how patterns of the use of place names reflect geospatial and geopolitical relationships of English-speaking nations. The second study concerns how the emotional connotation of words before place names reflects general well-being in that place. Taken together, these studies demonstrate that the surface structure of language, as embodied in word frequencies, is a useful source of information about the real world.
Keywords: corpus linguistics, sentiment analysis, cognitive maps, general-well being, World Englishes